Tax Sanctions And its Effectiveness in Overcoming with income tax evasion in Palestine - Ehab Khader Ahmad Mansour (My University, 2004)
This study deals with the phenomenon of income tax evasion in the Palestinian economy. It concentrates on the forms of income-tax evasion, their reasons and the role of the penalties legally enforced in resolving the problem. This study also stresses the impotence of income taxes to any economy and explains the effects of the none – payment of income taxes. It then present solutions to the problem, hoping that they will help policy makers in comparing the problem. The study depends on the relevant literature in formulating the theoretical framework. A questionnaire was designed to collect primary data on the issue of income tax evasion. The questionnaire contained 26 questions related to the issue and was distributed to a representative sample of the study population which is comprised of tax officials, accountants, and income tax payers. The data was analyzed using the SPSS statistical package. In addition, some interviews were conducted with officials of the tax departments.

هدفت هذه الرسالة على التعرف على طبيعة التهرب من ضريبة الدخل في فلسطين ومحاولة الكشف عن الأسباب التي تكمن وراء ذلك لما لهذه الظاهرة من آثار مدمرة على الاقتصاد الوطني. وفي هذه الدراسة قام الباحث بتناول الموضوع من خلال خمسة فصول حيث تطرق الفصل الأول إلى المالية العامة وأهميتها وخصائصها والضرائب على الدخل وأهميتها كجزء من المالية العامة. أما الفصل الثاني فقد خصص لمناقشة مشروع قانون ضريبة الدخل الفلسطيني المقترح. والفصل الثالث تناول ظاهرة التهرب من ضريبة الدخل في فلسطين. والفصل الرابع خصص للوسائل التي من الممكن إتباعها لمعالجة هذا التهرب وتم التركيز في هذا الفصل على العقوبات الضريبية كأساس لمحاربة هذا التهرب. أما الفصل الخامس فقد تم تخصيصه للجانب الإحصائي حيث قام الباحث بتصميم استبانة احتوت على (26) سؤال خاص بموضوع التهرب من ضريبة الدخل، وقد تم توزيع هذه الاستبانة على عينة عشوائية مثلت مجتمع الدراسة، وهذه العينة ضمت موظفي الضرائب والمنشآت الكبيرة والمحاسبين والمهنين (أطباء وأطباء أسنان ومهندسين ومحامين)، وهذه العينة مثلت (5%) من الفئات المذكورة حسب معطيات الجهاز المركزي للإحصاء الفلسطيني كما هو مبين في الملحق رقم (3) وبعد تفريغ البيانات تم التوصل إلى العديد من النتائج تم توضيحها والتركيز عليها في التوصيات وقد استخدم الباحث برنامج الرزم الإحصائية (SPSS) في تحليل البيانات لإيجاد النسبة المئوية لكل إجابة.
العقوبات الضريبية ومدى فاعليتها في مكافحة التهرب من ضريبة الدخل في فلسطين